Selection Process of School Principals in Indonesia and Some Other Countries - Sholeh, Muhamad; Windasari; Lestari, Dwi Nining; Widodo, Bambang Sigit (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The vital roles of school principals and the need for a professional selection and preparation process for school principals have encouraged the necessity of studying the process of preparing school principals in Indonesia. In developed countries, the main candidates are judged not only on their traditional management skills but also on their professional leadership skills. Principals are responsible for improving the quality of the schools they lead, so in developed countries, that becomes the main focus of assessment. In Indonesia, the policy for the preparation and selection process of school principals must be reviewed in a goal-oriented manner for the sake of improving education quality.  This research aimed to providing recommendations for improving the selection process of principals in Indonesia through a comparative analysis. Method in this research using literature review. This literature review collected data or sources related to a particular topic derived from various sources, such as journals, books, the internet, and other libraries. The results of the discussion indicated that there were similarities and differences in the selection processes for principals in Indonesia and the comparative countries in this study. Since the rules for selecting school principals in Indonesia often change, school principal candidates must always adapt to new regulations.